Makeup Training for Teenagers as a Form of Self-Confidence - MUNAWAROH, SANY; WAHYU SAPUTRA, ARDI; SULKAH RESPATI SIWI, LINTANG; RATNA PUTRI, ADE; NUR HIDAYAH, HANIFAH (JOURNAL INCLUSIVE SOCIETY COMMUNITY SERVIES, 2024)
Considering these conditions, it is necessary to hold make-up training for young women aged 17-23 years so that they can use age-appropriate make-up but still increase their self-confidence.This study aims to explore the impact of makeup training on adolescents' levels of self-confidence. In the context of modern society which increasingly pays attention to appearance, understanding the importance of self-confidence in teenagers is crucial. This research uses the interview method. Participants are involved in make-up training sessions which are held in a structured manner. The research results revealed a significant increase in teenagers' self-confidence levels after attending make-up training. Factors such as knowledge of make-up techniques, positive experiences, and social support from fellow participants played an important role in this improvement. The implications of this research can provide new insights in the development of training programs that can increase adolescent self-confidence through the application of makeup skills